Interdisciplinary Physician-Pharmacist Medication Review for Outpatients With Heart Failure: A Subanalysis of the PHARM-CHF Randomized Controlled Trial - Schumacher, Pia M.; Griese-Mammen, Nina; Schneider, Juliana; Laufs, Ulrich; Schulz, Martin (Frontiers in Pharmacology, 2021)
Aims: Patients with chronic heart failure (CHF) require polypharmacy and are at increased risk for drug-related problems. Interdisciplinary physician-pharmacist medication review may improve drug treatment. Our goal was to analyze the changes from the physician-documented medication plan (MP) and patient-stated medication to an interdisciplinary consolidated MP (CMP). Methods: This pre-specified subanalysis of the PHARM-CHF randomized controlled trial analyzed the medication review of CHF patients in the pharmacy care group. Community pharmacists compared the MP with the drug regimen stated by the patient and consulted with physicians on identified discrepancies and other medication-related problems resulting in a CMP. Results: We analyzed 93 patients (mean 74.0 ± 6.6 years, 37.6% female), taking a median of ten (IQR 8–13) drugs. 80.6% of patients had at least one change from MP to CMP. We identified changes in 32.7% (303/926) of drugs. The most common correction was the addition of a drug not documented in the MP to the CMP (43.2%). We also determined frequent modifications in the dosing regimens (37.6%). The omission of a drug documented in the MP but left out of the CMP accounted for 19.1%. Comparing patient-stated medication to CMP, the current drug regimen of patients was changed in 22.4% of drugs. Conclusion: The medication review resulted in changes of medication between MP and CMP in most of the patients and affected one-third of drugs. Structured physician-pharmacist interdisciplinary care is able to harmonize and optimize the drug treatment of CHF patients.